Multidisciplinary teams caring for people with variations of sex characteristics: a scoping review - Eva De Clercq; Martin Gramc; Jürg Streuli (BMJ Publishing Group, 2021)
Background In 2006 the Chicago consensus statement on the management of people with variations of sex characteristics (VSC) acknowledged the importance of a multidisciplinary team (MDT) approach. The consensus update from 2016 reinforced the call for multidisciplinary collaborations between medical professionals, parents and support groups, and proposed guidelines to improve shared decision making and patient-centred care embedded in ethical principles of self-determination and child participation. But there is little evidence that successfully MDTs have been implemented in clinical practice.Methods and aims A scoping review was conducted to identify studies that address the collaboration and decision making process of MDTs providing care of people with VSC to identify ideal and actual (1) team composition; (2) models of collaboration and (3) ethical principles that MDTs follow. Six databases were systematically searched: CINAHIL, Medline, Psychinfo, Scopus, Socindex and Web of Science. No restriction was placed on the type of methodology used in the studies. To frame the research, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses was used.Results The MDTs in the literature include mainly medical professionals: endocrinologists, urologists and surgeons. The collaboration among medical professionals in MDTs lacks cooperation as one team member sets the tasks of the team while each professional works separately. Despite the importance of psycho-social support the involvement of psychologists remains secondary. The implementation of ethical principles tends to exclude people with VSC.Conclusion The care of people with VSC described in the papers is medically oriented as the team members are mainly medical professionals working separately. MDT tend to exclude people with VSC despite references to shared decision making processes and informed consent. There was no mention of adult care and lack of inclusion of patient's perspective in the care process. The future research should do more empirical research of MDTs.